Peripheral nerve block in a migraine pregnant patient: a case report - Sampaio, Rhina de Freitas; Lira, Lucas Antônio Martins; Neri, Pedro Vinicius da Silva; Carvalho, Pedro Rubens Araújo; Queiroga, Morgana Feitosa de; Lima, Gabrielle Benevides; Guedes, Matheus da Costa; Assunção, Robson Caetano Guedes; Ribeiro, Ian Silva; Lôbo, Camila de Oliveira; Silva, Carla Welch da; Júnior, Luiz Gonzaga Nogueira; et al. (Headache Medicine, 2023)
Full abstract in PDF.